3D progressive evolution of a syncline depocentre from growth turbidite strata: the Annot syncline, SE France - Salles, L.; Ford, M.; Joseph, P. (TRABAJOS DE GEOLOGÍA, 2010)
The Annot syncline is one of the synclinal remnants of the Tertiary Alpine foreland basin,which was mainly structured during the Paleocene and filled during the Eocene-Oligocene by a marinetransgressive succession. The upper unit consists in the Annot Sandstone formation deposited in a fandelta-fed turbidite setting. New detailed structural data from the Annot depocentre indicate a progressivelimb rotation during deposition of the Annot Sandstone. These data are used to build a 3D modelof the syncline in Gocad software that documents turbidite depocentre evolution. Trishear modellingconstrains the role and interaction of regional thrusts and fault propagation folds in depocentre development.